Combined precompetitive mental conditioning model customized for pandemic-related limitations - Banayan, A.A.; Lashkul, A.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a new combined precompetitive psychological training model customizable for the pandemic-related limitations. Methods and structure of the study. In addition to the traditional live/ offline test equipment, the combined precompetitive mental conditioning model included an access to psychological information. At the end individual precompetitive mental conditioning plan was developed for a specific sports event. The popular social network VKontakte was used for the athletes from all over Russia who received an access to the precompetitive-mental-conditioning-related information and individualized precompetitive mental conditioning service to facilitate their trainings for specific events. Results and conclusion. Distance/ online precompetitive mental conditioning service formats have their benefits in at least the following domains: practical knowledge and guidance is accessible from any point of the globe; and the service is rather flexible and customizable for the individual training and competitive needs and goals. Such a service may be particularly efficient when combined with a reasonable direct/ live communication a sports psychologist with athlete at key points to facilitate competitive progress.